Polyketide genes in the marine sponge Plakortis simplex: a new group of mono‐modular type I polyketide synthases from sponge symbionts. Issue 6 (25th July 2013) - Della Sala, Gerardo; Hochmuth, Thomas; Costantino, Valeria; Teta, Roberta; Gerwick, William; Gerwick, Lena; Piel, Jörn; Mangoni, Alfonso
Summary Sponge symbionts are a largely unexplored source of new and unusual metabolic pathways. Insights into the distribution and function of metabolic genes of sponge symbionts are crucial to dissect and exploit their biotechnological potential. Screening of the metagenome of the marine sponge Plakortis simplex led to the discovery of the swf family, a new group of mono‐modular type I polyketide synthase/fatty acid synthase (PKS/FAS) specifically associated with sponge symbionts. Two different examples of the swf cluster were present in the metagenome of P. simplex. A third example of the cluster is present in the previously sequenced genome of a poribacterium from the sponge Aplysina aerophoba but was formerly considered orthologous to the wcb/rkp cluster. The swf cluster was also found in six additional species of sponges. Therefore, the swf cluster represents the second group of mono‐modular PKS, after the supA family, to be widespread in marine sponges. The putative swf operon consists of swfA (type I PKS/FAS), swfB (reductase and sulphotransferase domains) and swfC (radical S‐adenosylmethionine, or radical SAM). Activation of the acyl carrier protein (ACP) domain of the SwfA protein to its holo‐form by co‐expression with Svp is the first functional proof of swf type genes in marine sponges. However, the precise biosynthetic role of the swf clusters remains unknown.